Performances of Some Sorghum Genotypes Under Eskişehir Ecological Conditions - Şule ERKOVAN; Hanife AFACAN (ISPEC Journal of Agricultural Sciences)
The research was conducted in the 2023 growing season as a second crop after the wheat harvest, with the aim of determining the yield characteristics of some sorghum genotypes that can be grown under the ecological conditions of Eskişehir. The experiment was established according to the randomized complete block design with three replications. The study examined the number of days to 50% flowering, plant height, number of tillers per plant, stem diameter, leaf ratio, stem ratio in the plant, dry matter ratio, and green forage yield. Significant differences were found among the lines and varieties for all the studied traits. According to the research results, the days to 50% flowering of different varieties and lines ranged from 72.0 to 87.7 days, plant heights from 122.7 to 315.0 cm, the average number of tillers per genotype was 2.6, stem diameter ranged from 7.9 to 18.3 mm, leaf ratios from 10.9% to 22.9%, stem ratio from 77.1% to 89.6%, dry matter ratios from 15.6% to 30.9%, and green forage yields from 2152.0 to 5614.1 kg da-1. It is recommended to cultivate the Greengo and Erdurmuş varieties and the line number 12 in Eskişehir and similar ecological conditions in terms of green forage yield. However, more studies should be conducted, as single-year results do not always yield correct outcomes in agricultural production.